An optimal periodic scheduler for dual-arm robots in cluster tools with residency constraints. - Rostami, S. (IEEE Transactions on robotics and automation)
Discusses a scheduling technique, for cluster tools, that addresses postprocessing residency constraints and throughput requirements. The residency constraints impose a limit on the postprocessing time that a material unit spends in a processing module. The technique searches in the time and resource domains for a feasible schedule with a maximum throughput. It operates in two main phases; the initial one of which (and the lower complexity one) computes a simple periodic schedule. For a large number of problem instances, the simple periodic schedule feasibly solves the problem. If a feasible schedule cannot be found in the first phase, the scheduler enters phase two (the higher complexity one) to compute a feasible schedule. During this phase, the scheduler incrementally increases the period only if necessary, to keep the throughput at a maximum. Several heuristics are designed and added to reduce the complexity of the scheduling algorithm. The resulting schedules are deadlock free, since resources are scheduled according to the times that they are available. Analytical and experimental analyses demonstrate the correctness and efficiency of our proposed technique